2014
DOI: 10.1371/journal.pmed.1001751
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect of Vitamin D Binding Protein (DBP) Levels on Calcemic and Cardiometabolic Diseases: A Mendelian Randomization Study

Abstract: In this study, Richards and colleagues undertook a Mendelian randomization study to determine whether vitamin D binding protein (DBP) levels have a causal effect on common calcemic and cardiometabolic diseases. They concluded that DBP has no demonstrable causal effect on any of the diseases or traits investigated here, except Vit D levels. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 71 publications
(78 reference statements)
3
49
0
Order By: Relevance
“…MR analysis published by our group studying the association of vitamin D-binding protein, a key determinant of 25OHD levels, with the risk of CAD. 52 Using the single polymorphism rs2282679 near the GC gene as an instrumental variable (whose effect allele was associated with an age-and sex-adjusted decrease in vitamin D-binding protein level of 27.4 mg/L), this study investigated the relationship of vitamin D-binding protein with multiple cardiometabolic outcomes in the CARDIoGRAM consortium and found no association (OR, 1.02; 95% CI, 0.99-1.05; P=0.31). Using an approach related to MR, Jorde et al 61 examined causal associations of 25OHD with the risk of CAD on 9528 subjects, but could not establish or exclude any causal relationship, possibly because of their relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR analysis published by our group studying the association of vitamin D-binding protein, a key determinant of 25OHD levels, with the risk of CAD. 52 Using the single polymorphism rs2282679 near the GC gene as an instrumental variable (whose effect allele was associated with an age-and sex-adjusted decrease in vitamin D-binding protein level of 27.4 mg/L), this study investigated the relationship of vitamin D-binding protein with multiple cardiometabolic outcomes in the CARDIoGRAM consortium and found no association (OR, 1.02; 95% CI, 0.99-1.05; P=0.31). Using an approach related to MR, Jorde et al 61 examined causal associations of 25OHD with the risk of CAD on 9528 subjects, but could not establish or exclude any causal relationship, possibly because of their relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…51 Although it has been argued that vitamin D-binding protein, encoded by GC, can act independently of vitamin D to produce clinical phenotypes, this does not seem to be the case for CAD. 52 For rs12785878 (DHCR7), a large MR study on vitamin D levels and blood pressure showed a small but significant association with hypertension 53 (OR, 0.92; 95% confidence interval [CI], 0.87-0.97; P=0.001), a major risk factor for CAD. 54 By querying the results for rs12785878 in the ICBP consortium, 38 a large GWAS meta-analysis of 200 000 subjects of European descent, we found that this SNP was not associated with systolic or diastolic blood pressure (P=0.703 and P=0.121, respectively).…”
Section: Linkage Disequilibrium (Ld) and Pleiotropy Assessmentmentioning
confidence: 99%
“…A MR analysis was used by adopting a two-stage least-squares (2SLS) (Leong et al, 2014) estimator that regressed each outcome against predicted values of 25(OH)D level per composite GC SNP score using the command “ivreg2” in the Stata SE13.1 software package. This method allows for the estimation of the unconfounded association of genetically predicted concentrations of 25(OH)D with cognition.…”
Section: Methodsmentioning
confidence: 99%
“…The altered expression of DBP has also been observed in other autoimmune diseases with underlying vitamin D (un)related working mechanisms such as rheumatoid arthritis and [69] and granulomatosis with polyangiitis [26]. However in another Mendelian randomization study, DBP had no demonstrable causal effect on calcemic (osteoporosis and hyperparathyroidism) and cardiometabolic diseases (hypertension, type 2 diabetes, coronary artery disease and stroke) [70].…”
Section: Vitamin D Binding Protein: What's In a Name?mentioning
confidence: 95%